APPLICATION OF SPECTROSCOPIC TECHNIQUES (NIR AND RAMAN) IN THE NON-DESTRUCTIVE INSPECTION OF MEAT AND MILK: ADVANCES FOR THE SAFETY AND QUALITY OF PRODUCTS OF ANIMAL ORIGIN (International Seven Journal of Multidisciplinary, 2025)
Objective: To review the advances and applications of NIR and Raman spectroscopic techniques in the non-destructive inspection of meat and milk, highlighting their relevance to Veterinary Medicine, food safety and fraud prevention. The adulteration of food of animal origin represents a growing challenge for inspection services, requiring fast, sensitive and sustainable analytical methods. This review was based on scientific articles, dissertations, and theses published between 2010 and 2024, which address the use of near-infrared (NIR) spectroscopy and Raman spectroscopy in food, with an emphasis on integration with chemometric tools. The results demonstrate that NIR is effective in predicting the centesimal composition of meat and milk, while Raman spectroscopy has high specificity for wet matrix analysis. The association of these techniques with multivariate methods, such as PCA and PLS-DA, allows the detection of adulterations with an accuracy greater than 90%. The miniaturization of spectrometers and the use of portable equipment make these technologies applicable in real time in routine sanitary inspection. It is concluded that spectroscopy, combined with chemometrics, represents a strategic innovation for the quality control of products of animal origin, reinforcing the role of the veterinarian in ensuring food safety.